Research of trends of development of the health insurance market in the conditions of socio-economic crisis in Ukraine - Нala, Liliia; Panfilova, Hanna; Tsurikova, Oksana (ScienceRise: Pharmaceutical Science, 2019)
Aim: to analyze the development trends of the health insurance market in the context of the socio-economic crisis in Ukraine. Materials and methods. The studies used data from the National Commission for State Regulation of Financial Services Markets and the League of Insurance Organizations of Ukraine on the results of the activities of insurers (number of concluded contracts, gross, net premiums and payments) for 2014–2018. Financial indicators were standardized in accordance with macroeconomic standards that were established in state budgets for different years (minimum wage, minimum wage per person, NBU rate of 1 US dollar, minimum cost of a consumer basket). We used historical, analytical, comparative, systemic, logical, hypothetical-deductive, mathematical and statistical methods. Results. The significance of the relationship between all indicators is mathematically proven. In addition, all data for 2014–2018 showed positive growth dynamics. This cannot be argued after their normalization by macroeconomic indicators. According to the normalized data on the minimum wage, in 2017 there was a significant decrease in indicators with a slight increase compared to 2018. A positive fact is the growth of financial indicators during 2014-2018, which were normalized to the subsistence level for the working population. In 2015, there was a sharp decrease in the values of all financial indicators normalized at the dollar exchange rate, which is the result of fundamental changes in the monetary policy in the country. The indicated indicators reached the minimum value in 2016. The indicators normalized by the value of the minimum food basket showed a zigzag pattern of changes in all indicators with a sharp drop in data in 2016 and their subsequent increase in 2017. All indicators that were normalized by the minimum wage, the NBU dollar exchange rate, the value of the minimum food basket in 2018, did not reach the initial values typical for 2014. Conclusions. The health insurance market was characterized by complexity of development and dependence on the main macroeconomic indicators used in the calculation of many socially significant indicators of the development of society. Negative trends in the development of the segment of the health insurance market were due to the direct or delayed influence of changes observed in the macroeconomic environment during the socio-economic crisis